Skill mismatch and overeducation in transition economies - Olga Kupets (IZA World of Labor, 2015)
Large imbalances between the supply and demand for skills in transition economies are driven by rapid economic restructuring, misalignment of the education system with labor market needs, and underdeveloped adult education and training systems. The costs of mismatches can be large and long-lasting for workers, firms, and economies, with long periods of overeducation implying a loss of human capital for individuals and ineffective use of resources for the economy. To make informed decisions, policymakers need to understand how different types of workers and firms are affected by overeducation and skill shortages.
Keywords: I25; J08; J24; P23; 330; overeducation; skills development; transition countries